Strategies for Anticipating Speech Production Errors in the Public Speaking Context: Psycholinguistic Analysis and Improving Public Speaking Ability - Cahyandari, Rini; vimelia, willen; salih, yasir (International Journal of Linguistics, Communication, and Broadcasting, 2024)
This research explores and analyzes various aspects related to public speaking and speech production errors in real life contexts. Through a literature review, this research explains the types of speech production errors, their causes, and strategies to anticipate these errors. This research also links speech production errors with public speaking, highlighting the importance of psycholinguistic understanding in this regard. The research results show that anticipating speech production errors is the key to improving public speaking skills. Anticipation strategies include preparing the topic well, maintaining composure, focusing, and using familiar vocabulary. Speech production errors can disrupt the flow of a presentation, so a deep understanding of these aspects is very important in public speaking.